Children’s and Adults’ Perceptions of Religious and Secular Interventions for Incarcerated Individuals in the United States - Cohen, Aaron (Religions, 2023)
Religious involvement is prevalent in prisons, a context where questions of moral redemption are particularly salient. We probed the developmental origins of adults’ perceptions that religion might lead to redemption following transgressions. Six- to eight-year-olds (n = 50 United States residents) and adults (n = 53 United States residents) learned about incarcerated characters who had taken religion classes, art classes, or life classes (about right and wrong) while imprisoned. They then rated their agreement with statements assessing attitudes toward the incarcerated individuals, the effectiveness of each character’s time in prison, and their likelihood of recidivism. Children were more likely than adults to report that classes, in general, would effectively rehabilitate incarcerated individuals. However, participants of all ages reported more positive attitudes toward people who took religion classes and life classes rather than art classes. Further, participants of all ages reported that people who took art classes, versus religion or life classes, would be more likely to continue transgressing. These findings highlight the important role that religious and secular learning plays in perceptions of redemption across development.